A Study On Assessment Of Quality Procedure And Practices Adopted Among Hospitals In Rohilkhand Region (Journal of Pharmaceutical Negative Results, 2022)
The classification of biomedical wastes based on the source from which they are created includes many risk factor related to their handling and eventual disposal. A tertiary care hospital's compliance with various categories of biomedical waste management was assessed. A checklist with 17 biomedical waste management-related criteria, including "condition of waste containers," "segregation of waste," and "mutilation of recyclable waste," was created and compliance was monitored in 70 different patient care settings, including wards, casualty departments, operating rooms, and intensive care units. During the two-month study period from 1 November to 31 December 2021, any three non-consecutive days were used to visit each area. Thus, a total of 30 visits were made to area and mean percentage score was analysed for each area and each category of biomedical waste management. For Medicity Hospital OTs,Wards, Casualty, and ICU the mean percentage was 90%, 90.67%, 94.64 and 92.17% respectively. In Ram Ganga Hospital, the mean percentage was 88.67%, 91.34%, 92.34 and 91% respectively. For Vaidic Hospital, the mean percentage for these categories was 74.67%, 85.34%, 73.34% and 78% respectively. It was determined that more importance needs to be rested for ‘mutilation of recyclable waste’ especially in wards.